MODIFIKASI MORDENIT TERAKTIVASI HNO3 DENGAN AMINOPROPILTRIMETOKSISILAN UNTUK ADSORPSI ION Cu(II) - , ENI KURNIAWATI, Prof. Wega Trisunaryanti, M.S., Ph.D. Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Modification of HNO3-activated mordenite (ZM) by aminopropyltrimetoxysilane (APTMS) for adsorption of Cu(II) cation has been studied. Four gram of mordenite was refluxed in 20 mL of 6 M HNO3 solution for 30 and 120 min, and produced the ZM1 and ZM2 samples respectively. The samples were then modified using APTMS by grafting methode. The samples were characterized by Fourier Transformed Infra Red (FTIR) spectrometry and X-ray Diffraction (XRD) to analyze âNH2 functional groups and crystallinity respectively. The modified samples were applied for adsorption of Cu(II) cation. Concentration of unadsorbed Cu(II) in solution was analyzed by Atomic Absorption Spectroscopy (AAS). The reaction kinetic and isotherm model were also studied. The results showed that Si/Al ratio has increased from 4.6 for ZM to 14.7 for ZM1 and 18.0 for ZM2. The success of grafting process was indicated by the FTIR spectra which shown by the appearance of peak at wave number of 2939 cm-1 for streching vibration of âCH2 and 1573 cm-1 for bending vibration of âNH2. The adsorption capacity of ZM